THE CORRELATION BETWEEN SPEAKING ANXIETY AND SPEAKING ACHIEVEMENT - Eksanti Oktavia Putri; Ridha Ilma; Fitri Alya Okta Sukma (PROJECT (Professional Journal of English Education), 2023)
Speaking is one of the most essential skills students must acquire, but they may experience anxiety when communicating in English. If a student is nervous about speaking, it could make it harder for them to do well. Hence, this research examined the correlation and influence of speaking anxiety and speaking achievement among a sample of tenth grade students with 30 students in a state vocational school in Palembang. The participants were selected using cluster random selection. The researchers utilized the Foreign Language Speaking Anxiety Questionnaire (FLSAQ) to assess speaking anxiety levels. Additionally, a speaking assessment was conducted to assess students' proficiency in speaking. The result revealed no statistically significant relationship between speaking anxiety and speaking achievement, as determined by (sig. 2-tailed) > 0.05. The result suggested that H0_1 was accepted and Hα_1 was rejected.